(untitled) (Journal of the College of Basic Education, 2022)
The research is devoted to explaining the role of exposure, perception, interpretation, and selective recollection of the recipient and the conditions according to which the individual identifies and chooses communication materials and programs and their effectiveness by influencing the determination of his behavioral pattern as well as his direction of the materials he is exposed to. The role of mediating factors in shaping the perceptual structure of the recipients and the expectations of individuals depends on the groups and the frame of reference and linking that to the approaches to the theory of cognitive dissonance.